THE IMPACT OF THE KETEL PARIGI WHITE OIL INDUSTRY ON INCREASING COMMUNITY WELFAREIN BURU DISTRICT - Derek Bakarbessy (JURNAL BADATI, 2022)
This study aims to explain the impact of the Ketel Parigi eucalyptus oil industry on improving the welfare of the people in Buru Regency. This research is a survey research, where data collection is done by using a questionnaire. The results of the study indicate that the impact of the Parigi Ketel Ketel eucalyptus oil industry has an effect on improving the welfare of the people in Buru Regency. However, this increase in welfare can only be seen clearly in the increase in income, while the improvement and improvement of health and educational facilities, as well as transportation facilities have received less serious attention. In addition, the impact of the existence of the Parigi Ketel eucalyptus oil industry has an effect on improving people's welfare, namely the expansion of job opportunities.